Barrier film, and wavelength conversion sheet, backlight, and liquid crystal display using the same
Patent Information
- Application Number
- KR1020237008934
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-08-19
- Filing Date
- 2021-08-03
- Publication Date
- 2026-09-01
- Estimated Expiration
- 2041-08-03
Smart Images

Figure 112023029050319-PCT00004_ABST
Abstract
Description
Technology Field
[0001] The present disclosure relates to a barrier film, a wavelength conversion sheet using the same, a backlight, and a liquid crystal display device. Background Technology
[0002] As personal computers, such as portable personal computers, develop, the demand for liquid crystal displays is increasing. Furthermore, the penetration rate of home LCD televisions has recently risen, and smartphones and tablet devices are also becoming widely available. Consequently, the liquid crystal display market is expanding further.
[0003] Such liquid crystal display devices generally consist of a configuration comprising a color filter, a liquid crystal cell, and a backlight. Furthermore, the liquid crystal display device typically displays an image by controlling the intensity of light through the shutter function of the liquid crystal layer within the liquid crystal cell and by dividing the color of each pixel into the three primary colors of R, G, and B using a color filter.
[0004] Cold cathode tubes have traditionally been used as backlight sources for liquid crystal displays. However, from the perspective of low power consumption and space saving, backlight sources are being switched from cold cathode tubes to LEDs.
[0005] LEDs used as conventional backlight sources utilize what are called white LEDs, which are formed by combining a blue LED with a YAG-based yellow phosphor. These white LEDs are referred to as pseudo-white because the spectral distribution of their emission wavelengths is broad.
[0006] Meanwhile, the development of backlights using quantum dot technology is also underway. Quantum dots refer to nanometer-sized semiconductor particles.
[0007] The basic configuration of a backlight using quantum dots is a combination of a light source that generates primary light (such as a blue LED emitting blue light) and quantum dots.
[0008] Quantum dots are nano-sized compound semiconductor particles composed of a semiconductor particle consisting of, for example, a core of CdSe and a shell of ZnS, and a ligand covering the shell. Since the particle diameter of a quantum dot is smaller than the Bohr radius of an exciton in a compound semiconductor, a quantum confinement effect occurs. Therefore, the luminescence efficiency of quantum dots is higher than that of phosphors using rare earth ions as activators, which are conventionally used, and can achieve a high luminescence efficiency of over 90%.
[0009] In addition, since the emission wavelength of the quantum dot is determined by the bandgap energy of the quantized compound semiconductor microparticles, any emission spectrum can be obtained by changing the particle size of the quantum dot. A backlight combining these quantum dots with blue LEDs can achieve high color purity with high luminous efficiency (see, for example, Patent Documents 1 and 2).
[0010] While quantum dots possess the aforementioned excellent characteristics, they have the problem of being susceptible to degradation due to the influence of moisture, oxygen, etc. For this reason, it is desirable to protect both sides of the quantum dot-containing layer with a barrier film.
[0011] Patent documents 3 and 4 propose a wavelength conversion sheet formed by protecting a quantum dot-containing layer by a barrier film having a substrate, an inorganic oxide layer, and an organic coating layer. Prior art literature
[0012] Patent Document 1: International Publication No. 2012 / 132239 Patent Document 2: Japanese Patent Publication No. 2015-18131 Patent Document 3: Japanese Patent Publication No. 2019-126924 Patent Document 4: Japanese Patent Publication No. 2020-19141 The problem to be solved
[0013] However, in the liquid crystal display device using the wavelength conversion sheet of Patent Documents 3 and 4, there were occasional cases where an image with a different color tone from the initial state was visible during continuous use. That is, in the liquid crystal display device using the wavelength conversion sheet of Patent Documents 3 and 4, there were occasional cases where the color tone was significantly different when comparing the initial state with an arbitrary point in time. Quantum dots are characterized by increasing color purity. For this reason, the unstable color tone of the liquid crystal display device using quantum dots was a very critical quality issue, as it damaged the characteristics of the liquid crystal display device.
[0014] The present disclosure aims to provide a barrier film capable of suppressing changes in color tone when applied to a wavelength conversion sheet, in light of the above problem. Furthermore, the present disclosure aims to provide a wavelength conversion sheet, a backlight, and a liquid crystal display device using the barrier film. means of solving the problem
[0015] As a result of diligent research to solve the above problem, the inventors discovered that swelling of the organic coating layer of the barrier film when a wavelength conversion sheet with a barrier film applied is exposed to a high-humidity environment is one cause of the color change. Therefore, the inventors considered reducing the thickness of the organic coating layer to a level that does not affect the barrier properties. However, many cases occurred in which the color changed even when the thickness of the organic coating layer was reduced.
[0016] Therefore, the inventors have further investigated and found that by setting the thickness of the organic coating layer to a predetermined range and also setting the ratio of the thickness of the primer layer formed to improve adhesion with the quantum dot-containing layer to the thickness of the organic coating layer to a predetermined range, color change of the wavelength conversion sheet, etc., to which the barrier film is applied can be suppressed.
[0017] The present disclosure provides the following [1] to [6].
[0018] [1] On a light-transmitting substrate, an inorganic oxide layer A, an organic coating layer B, an inorganic oxide layer C and a primer layer D are arranged in this order,
[0019] The thicknesses of the light-transmitting substrate, the inorganic oxide layer A, the organic coating layer B, the inorganic oxide layer C, and the primer layer D are respectively t0 and t A , t B , t C and t D When defined as,
[0020] t B α is 150 nm or more and 500 nm or less, and also,
[0021] t D / t B A barrier film for wavelength conversion sheets having a value of 0.55 or higher and 1.65 or lower.
[0022] [2] The barrier film described in [1], wherein the inorganic oxide layer A and the inorganic oxide layer C contain aluminum oxide or silicon oxide.
[0023] [3] The barrier film described in [1] or [2], wherein the organic coating layer B comprises polyvinyl alcohol.
[0024] [4] A wavelength conversion sheet having a quantum dot containing layer containing quantum dots and a barrier film laminated on both sides of the quantum dot containing layer, wherein the barrier film is laminated such that the side opposite to the light-transmitting surface of the barrier film described in any one of [1] to [3] faces the quantum dot containing layer.
[0025] [5] A backlight comprising at least one light source emitting primary light, an optical plate disposed adjacent to the light source for guiding or diffusing light, and a wavelength conversion sheet disposed on the light-emitting side of the optical plate, wherein the wavelength conversion sheet is the wavelength conversion sheet described in [4].
[0026] [6] A liquid crystal display device having a backlight and a liquid crystal panel, wherein the backlight is the backlight described in [5]. Effects of the invention
[0027] The barrier film of the present disclosure, and the wavelength conversion sheet, backlight, and liquid crystal display device using the same, can suppress changes in color tone. Brief explanation of the drawing
[0028] FIG. 1 is a cross-sectional view illustrating one embodiment of a barrier film according to the present disclosure. FIG. 2 is a cross-sectional view illustrating one embodiment of a wavelength conversion sheet according to the present disclosure. FIG. 3 is a cross-sectional view illustrating one embodiment of a backlight according to the present disclosure. FIG. 4 is a cross-sectional view illustrating another embodiment of a backlight according to the present disclosure. Specific details for implementing the invention
[0029] Hereinafter, embodiments of the present disclosure will be described.
[0030] In addition, the notation “AA~BB” in this specification means AA or higher and BB or lower.
[0031] In addition, in this specification, the refractive index of each layer refers to the refractive index at a wavelength of 632.8 nm. The refractive index of each layer can be calculated, for example, by fitting a reflection spectrum measured by a reflectometer and a reflection spectrum calculated from an optical model of a multilayer thin film using Fresnel coefficients.
[0032] Barrier Film
[0033] The barrier film of the present disclosure is,
[0034] On a light-transmitting substrate, an inorganic oxide layer A, an organic coating layer B, an inorganic oxide layer C, and a primer layer D are arranged in this order,
[0035] The thicknesses of the light-transmitting substrate, the inorganic oxide layer A, the organic coating layer B, the inorganic oxide layer C, and the primer layer D are respectively t0 and t A , t B , t C and t D When defined as,
[0036] t B α is 150 nm or more and 500 nm or less, and also,
[0037] t D / t B α is 0.55 or greater and 1.65 or less, and
[0038] It is used in wavelength conversion sheets.
[0039] FIG. 1 is a cross-sectional view illustrating an embodiment of the barrier film (100) of the present disclosure. The barrier film (100) of FIG. 1 has an inorganic oxide layer A (21), an organic coating layer B (30), an inorganic oxide layer C (22), and a primer layer D (40) in this order on a light-transmitting substrate (10).
[0040] Light-transmitting material
[0041] As for the light-transmitting substrate, any resin film that does not impair the function of the wavelength conversion sheet when applied to the wavelength conversion sheet is not particularly limited.
[0042] Examples of light-transmitting substrates include resin films formed from one or more resins selected from polyester, triacetylcellulose (TAC), cellulose diacetate, cellulose acetate butyrate, polyamide, polyimide, polyethersulfone, polysulfone, polypropylene, polymethylpentene, polyvinyl chloride, polyvinyl acetal, polyetherketone, acrylic, polycarbonate, polyurethane, and amorphous olefin (Cyclo-Olefin-Polymer: COP).
[0043] Among these resin films, in terms of mechanical strength, dimensional stability, and heat resistance, a polyester film that has undergone stretching, particularly biaxial stretching, is preferred. Examples of polyester films include polyethylene terephthalate films and polyethylene naphthalate films.
[0044] The light-transmitting substrate may be a single layer of resin film or may comprise multiple resin films. In the case of multiple resin films, each resin film may be directly bonded or bonded through an adhesive layer.
[0045] The thickness t0 of the light-transmitting substrate is preferably 5 μm or more, more preferably 8 μm or more, and even more preferably 10 μm or more. By making the thickness of the light-transmitting substrate 5 μm or more, it is easier to improve the strength of the barrier film.
[0046] In addition, the thickness t0 of the light-transmitting substrate is preferably 200 μm or less, more preferably 150 μm or less, more preferably 100 μm or less, more preferably 50 μm or less, and more preferably 25 μm or less, from the perspective of facilitating thinning and suppressing the intrusion of water vapor and oxygen from the ends.
[0047] In the present specification, the thickness of each layer constituting the barrier film, such as the thickness t0 of the light-transmitting substrate, and the thickness of the quantum dot-containing layer can be calculated by measuring the thickness at 20 locations from a cross-sectional image taken using, for example, a scanning transmission electron microscope (STEM), and calculating the average value of the 20 values.
[0048] In this specification, when measuring various parameters such as the thickness of each layer, total light transmittance, and color tone (x and y values of the Yxy color system), unless specifically requested otherwise, the measurements shall be taken in an atmosphere with a temperature of 23℃±5℃ and a relative humidity of 40% or more and 65% or less. In addition, before measuring various parameters, the sample shall be exposed to the above atmosphere for at least 30 minutes.
[0049] In addition, regarding the configuration requirements described in this specification, if there are multiple options for an upper limit and a lower limit of a numerical value, one selected from the upper limit option and one selected from the lower limit option can be combined to form an embodiment of the numerical range. For example, in the case of the thickness t0 of the light-transmitting substrate described above, embodiments of numerical ranges such as 5 μm or more and 200 μm or less, 5 μm or more and 25 μm or less, 8 μm or more and 50 μm or less, 10 μm or more and 50 μm or less, and 10 μm or more and 25 μm or less may be cited.
[0050] When a light-transmitting substrate is formed using two resin films, the thickness of the first resin film on the side closer to the inorganic oxide layer A is preferably 5 μm or more and 50 μm or less, more preferably 8 μm or more and 25 μm or less, and even more preferably 10 μm or more and 20 μm or less. If the first resin film has the above thickness, it is easier to improve the manufacturing efficiency of the inorganic oxide layer and also easier to improve the handling properties.
[0051] In addition, the thickness of the second resin film on the far side of the inorganic oxide layer A is preferably 5 μm or more and 150 μm or less, more preferably 8 μm or more and 100 μm or less, and even more preferably 10 μm or more and 50 μm or less. If the second resin film has the above thickness, it is easier to achieve a good balance of handling properties and rigidity of the barrier film.
[0052] When a light-transmitting substrate is formed using two resin films, the two resin films may be bonded together through an adhesive layer and then an inorganic oxide layer A, etc. may be formed, or an inorganic oxide layer A, etc. may be formed on the first resin film and then a second resin film may be bonded to the side opposite to the inorganic oxide layer A, etc. of the first resin film through an adhesive layer. The thickness of the adhesive layer is preferably 3 μm or more and 100 μm or less, more preferably 3 μm or more and 50 μm or less, and even more preferably 4 μm or more and 8 μm or less. If the thickness of the adhesive layer is excessively thin, coating defects may occur, and if the thickness is excessively thick, insufficient curing may occur.
[0053] The light-transmitting substrate preferably has a total light transmittance of 80% or more according to JIS K7361-1:1997, more preferably 85% or more, and even more preferably 87% or more.
[0054] On the surface of the side where the inorganic oxide layer A of the light-transmitting substrate is formed, a desired surface treatment may be performed in advance to improve adhesion, etc. Examples of surface treatments include corona discharge treatment, ozone treatment, low-temperature plasma treatment using oxygen gas or nitrogen gas, glow discharge treatment, and oxidation treatment using chemical agents.
[0055] Inorganic oxide layer
[0056] The barrier film of the present disclosure has an inorganic oxide layer A and an inorganic oxide layer C as inorganic oxide layers. By having two inorganic oxide layers in this way, the barrier properties of the barrier film against oxygen and water vapor can be improved, making it easier to suppress the degradation of quantum dots. Furthermore, if one attempts to improve barrier properties with a single inorganic oxide layer, the thickness of the inorganic oxide layer becomes thick, making it easy for cracks to form in the inorganic oxide layer, which makes it difficult to maintain good barrier properties over a long period of time. However, by using two inorganic oxide layers, the thickness of each inorganic oxide layer is suppressed, making it difficult for cracks to form, and thus making it easier to maintain good barrier properties over a long period of time.
[0057] In addition, cracks or pinholes may occur even if the thickness of the inorganic oxide layer is reduced. However, even if cracks or pinholes occur in each of the two inorganic oxide layers, as long as the locations of the cracks or pinholes do not coincide in the planar direction, the laminate can provide a predetermined barrier property. In other words, using two inorganic oxide layers is desirable in that it is easy to provide a predetermined barrier property even if cracks or pinholes occur in the inorganic oxide layers.
[0058] Inorganic oxide layer A and inorganic oxide layer C may be exemplified by layers composed of one selected from aluminum oxide, magnesium oxide, indium tin oxide (ITO), and silicon oxide, or a mixture thereof. The compositions of inorganic oxide layer A and inorganic oxide layer C may be the same or different.
[0059] Inorganic oxide layer A and inorganic oxide layer C are preferably layers containing aluminum oxide or silicon oxide from the perspective of transparency and productivity.
[0060] In addition, it is preferable that at least one of the inorganic oxide layer A and the inorganic oxide layer C is a layer containing aluminum oxide for the sake of sufficient barrier properties, transparency, and productivity, and it is more preferable that both the inorganic oxide layer A and the inorganic oxide layer C are layers containing aluminum oxide.
[0061] The content ratio of aluminum oxide or silicon oxide in the inorganic oxide layer A or inorganic oxide layer C is preferably 80 mass% or more on a mass basis, more preferably 90 mass% or more, and even more preferably 95 mass% or more.
[0062] Examples of embodiments regarding the combination of inorganic oxide layer A and inorganic oxide layer C include the following (1) to (4).
[0063] (1) An embodiment in which both inorganic oxide layer A and inorganic oxide layer C are layers containing aluminum oxide
[0064] (2) An embodiment in which both inorganic oxide layer A and inorganic oxide layer C are layers containing silicon oxide
[0065] (3) An embodiment in which inorganic oxide layer A is a layer containing aluminum oxide and inorganic oxide layer C is a layer containing silicon oxide
[0066] (4) An embodiment in which inorganic oxide layer A is a layer containing silicon oxide and inorganic oxide layer C is a layer containing aluminum oxide
[0067] Among the above (1) to (4), (1), (3) and (4) are preferred from the perspective of barrier properties, and (1) is more preferred.
[0068] Meanwhile, the barrier film may be laminated with other components, and a predetermined tension is applied to the barrier film during lamination. The crack resistance against the above tension is superior in the layer containing silicon oxide than in the layer containing aluminum oxide. Therefore, from the perspective of crack resistance against the above tension, (2) to (4) are preferred, and (2) is more preferred.
[0069] In the above respects, (3) and (4) are desirable in terms of the balance between barrier properties and the crack prevention properties of the inorganic oxide layer against tension. Additionally, a layer containing silicon oxide tends to be more prone to developing pinholes when forming the inorganic oxide layer than a layer containing aluminum oxide. When comparing (3) and (4), (4) is desirable in that even if pinholes occur in the layer containing silicon oxide, the pinholes are filled by the organic coating layer B, making it easier to maintain barrier properties.
[0070] The barrier properties of the inorganic oxide layer tend to deteriorate if the thickness is excessively thin, and tend to become susceptible to scratches and cracks if the thickness is excessively thick. The thickness t of the inorganic oxide layer A A and thickness t of inorganic oxide layer C C It is desirable to set the range appropriately according to the material of the inorganic oxide layer so that the balance of barrier properties, wound inhibition, and crack inhibition is good.
[0071] For example, if inorganic oxide layer A and inorganic oxide layer C are layers containing aluminum oxide, t A and t C It is preferable that the lower limit of each is 6 nm or more, and more preferable that it is 7 nm or more. A and t C By making the thickness 6 nm or more, it is easier to improve barrier properties.
[0072] Also, t A and t CEach is preferably 25 nm or less, more preferably 20 nm or less, more preferably 15 nm or less, more preferably 12 nm or less, and more preferably 10 nm or less. A and t C By making the thickness 25 nm or less, it is possible to easily suppress the occurrence of scratches and cracks in the inorganic oxide layer A and the inorganic oxide layer C.
[0073] In addition, if inorganic oxide layer A and inorganic oxide layer C are layers comprising one or more of silicon oxide, magnesium oxide, and indium tin oxide (ITO), t A and t C It is preferable that the lower limit of each is 20 nm or more, more preferable that it is 25 nm or more, and more preferable that it is 27 nm or more. A and t C By making the thickness 20 nm or more, it is easier to improve barrier properties.
[0074] Also, t A and t C Each is preferably 100 nm or less, more preferably 75 nm or less, even more preferably 60 nm or less, and even more preferably 50 nm or less. A and t C By making the thickness 100 nm or less, it is easier to suppress the occurrence of scratches and cracks in the inorganic oxide layer A and the inorganic oxide layer C.
[0075] The inorganic oxide layer can be formed by physical vapor phase growth methods, such as vacuum deposition, sputtering, and ion plating, or chemical vapor phase growth methods, such as plasma chemical vapor phase growth, thermochemical vapor phase growth, and photochemical vapor phase growth. Among these, vacuum deposition is preferred due to its fast deposition rate and good productivity.
[0076] Organic coating layer
[0077] The barrier film of the present disclosure has an organic coating layer B as an organic coating layer. By having an organic coating layer in combination with an inorganic oxide layer, the barrier properties of the barrier film can be improved, and the degradation of quantum dots can be easily suppressed. In addition, since the organic coating layer has good flexibility compared to the inorganic oxide layer, the occurrence of scratches and cracks in the inorganic oxide layer A and inorganic oxide layer C can be easily suppressed by the organic coating layer B. It is preferable that the organic coating layer B is in contact with the inorganic oxide layer A and inorganic oxide layer C in the thickness direction of the barrier film.
[0078] Thickness t of organic coating layer B B It needs to be between 150 nm and 500 nm. B It is preferable that the length is 175 nm or more and 450 nm or less, and more preferable that the length is 200 nm or more and 400 nm or less.
[0079] t B If the thickness is less than 150 nm, the barrier properties of the barrier film are insufficient, and the quantum dots in the quantum dot-containing layer deteriorate, causing the color to change over time.
[0080] Also, t B If α exceeds 500 nm, barrier issues are unlikely to occur, but changes in color cannot be suppressed. BWhen the amount increases, the change in thickness due to swelling of the organic coating layer B under high humidity conditions increases. Because of this, the action of thin film interference changes significantly, and it is thought that the change in color tone cannot be suppressed as the waveform of the spectral transmittance of the barrier film shifts. To explain in more detail, the spectral transmittance of the barrier film has different values for each wavelength and increases or decreases at a predetermined period. Therefore, when the organic coating layer B swells and the waveform of the spectral transmittance of the barrier film shifts toward the long wavelength side or the short wavelength side, the spectral transmittance of a specific wavelength (e.g., wavelength 450 nm) changes, and thus the color tone changes.
[0081] Also, t B If it is excessively thick, the stress generated when the organic coating layer is applied and dried increases, and due to this stress, cracks may form in the inorganic oxide layer, which may lead to a decrease in barrier performance. For this reason, t B By making the initial barrier properties good, it is possible to make it easier to achieve good initial barrier properties.
[0082] It is preferable that the organic coating layer B comprises one or more selected from water-soluble polymers and metal alkoxide-based compounds. Furthermore, it is more preferable that the organic coating layer B comprises one or more selected from water-soluble polymers among water-soluble polymers and metal alkoxide-based compounds, and it is even more preferable that it comprises one or more selected from water-soluble polymers and one or more selected from metal alkoxide-based compounds.
[0083] Examples of water-soluble polymers include polyvinyl alcohol, polyvinylpyrrolidone, and ethylene-vinyl alcohol copolymers. Among these, polyvinyl alcohol and ethylene-vinyl alcohol copolymers are preferred from the perspective of barrier properties, and polyvinyl alcohol is more preferred. That is, organic coating layer B preferably comprises one or more selected from polyvinyl alcohol and ethylene-vinyl alcohol copolymers, and it is more preferable to comprise polyvinyl alcohol.
[0084] When the organic coating layer B contains a water-soluble polymer and a metal alkoxide-based compound, the content of the water-soluble polymer per 100 parts by mass of the total amount of the metal alkoxide-based compound is preferably 5 parts by mass or more and 500 parts by mass or less, more preferably 7 parts by mass or more and 100 parts by mass or less, and even more preferably 8 parts by mass or more and 50 parts by mass or less.
[0085] Examples of metal alkoxide-based compounds include metal alkoxides, metal alkoxide hydrolysates, and metal alkoxide polymers.
[0086] Metal alkoxides are, M(OR) n It is a compound represented by the general formula. In the formula, M represents a metal such as Si, Ti, Al, and Zr, and R represents an alkyl group such as a methyl group and an ethyl group. Specific examples of metal alkoxides include tetramethoxysilane, tetraethoxysilane, and isopropoxyaluminum.
[0087] The organic coating layer B can be formed, for example, by applying and drying a coating solution containing components constituting the organic coating layer B onto an inorganic oxide layer. The coating solution may contain additives such as a silane coupling agent, a curing agent, and a dispersant.
[0088] Primer layer
[0089] The barrier film of the present disclosure needs to have a primer layer D on the side opposite to the organic coating layer B of the inorganic oxide layer C. By having a primer layer, the adhesion between the barrier film and the quantum dot-containing layer is improved, making it easier to maintain the barrier properties of the barrier film over a long period, thereby suppressing color changes over time. In addition, it can be expected that the primer layer D makes it easier to suppress the occurrence of scratches and cracks in the inorganic oxide layer C.
[0090] It is preferable to position the primer layer in contact with the inorganic oxide layer C. Additionally, it is preferable to position the primer layer on the outermost layer of the barrier film.
[0091] The barrier film of the present disclosure has a primer layer D with a thickness t D and the thickness t of the organic coating layer B B The non-invariant t D / t B t needs to be between 0.55 and 1.65. D / t B It is preferable that it be 0.60 or more and 1.50 or less, and more preferable that it be 0.70 or more and 1.30 or less.
[0092] t D / t B If α is less than 0.55, when stress is generated due to the barrier film stretching or other factors, an excessive load is applied to the thin primer layer D, making the interface of the primer layer D prone to delamination. In addition, t D / t B When the value exceeds 1.65, when stress is generated due to the barrier film stretching or other factors, an excessive load is applied to the thin organic coating layer B, making it easy for the interface of the organic coating layer B to peel off.
[0093] That is, t D / t B Since the value is between 0.55 and 1.65, it is possible to suppress the application of an excessive load to one side of the organic coating layer B and the primer layer D when stress occurs, thereby making it easier to maintain the barrier properties of the barrier film over a long period of time and to suppress changes in color over time.
[0094] Thickness t of primer layer D D is t D / t B If it is 0.55 or higher and 1.65 or lower, it is not specifically limited.
[0095] t DThe wavelength is typically 82.5 nm or more and 825 nm or less, preferably 100 nm or more and 600 nm or less, and more preferably 125 nm or more and 400 nm or less.
[0096] "furtherance"
[0097] It is preferable that the primer layer D includes a resin component such as a polyurethane-based resin composition. The polyurethane-based resin facilitates good adhesion with the quantum dot-containing layer and also relieves stress generated when the quantum dot-containing layer is cured by ionizing radiation or heat curing, thereby making it difficult for said stress to be transmitted to the inorganic oxide layer and the organic coating layer. In addition, the polyurethane-based resin improves the elongation of the primer layer D, making it easier to suppress the formation of cracks in layers constituting the barrier film, such as the inorganic oxide layer.
[0098] Examples of polyurethane resin compositions include one- or two-component polyurethane resin compositions obtained by the reaction of a polyfunctional isocyanate and a hydroxyl group-containing compound. The polyfunctional isocyanate and the hydroxyl group-containing compound may each be used as a single type or as multiple types.
[0099] Specifically, examples of multifunctional isocyanates include aromatic polyisocyanates such as tolylene diisocyanate, diphenylmethane diisocyanate, xylylene diisocyanate, and polymethylene polyphenylene polyisocyanate, or aliphatic polyisocyanates such as hexamethylene diisocyanate and isophorone diisocyanate.
[0100] In addition, hydroxyl group-containing compounds may include polyether polyols, polyester polyols, polyester polyurethane polyols, polyacrylate polyols, etc. In the present disclosure, polyester polyurethane polyols are particularly preferred in terms of adhesion and durability with the quantum dot-containing layer. Polyester polyurethane polyols can be manufactured, for example, by the method described in Japanese Patent Publication No. 2001-288408 and Japanese Patent Publication No. 2003-26996.
[0101] The content of the polyurethane resin composition is preferably 40 mass% or more based on the total amount of primer layer D, and more preferably 70 mass% or more.
[0102] Primer layer D may additionally contain a silane coupling agent. By including a silane coupling agent, it is easier to improve the adhesion between primer layer D and inorganic oxide layer C. The functional group at one end of the silane coupling agent, typically a chloro, alkoxy, or acetoxy group, hydrolyzes to form a silanol group (Si-OH). As a result, the resin composition of primer layer D is modified by covalent bonds, etc., to form a strong bond. Furthermore, organic functional groups such as vinyl, methacrylate, amino, epoxy, or mercapto at the other end of the silane coupling agent can be used to easily improve the adhesion between primer layer D and inorganic oxide layer C, and between primer layer D and the dot-containing layer.
[0103] Examples of silane coupling agents include γ-chloropropyltrimethoxysilane, vinyltrichlorosilane, vinyltriethoxysilane, vinyl-tris(β-methoxyethoxy)silane, γ-methacryloxypropyltrimethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, vinyltriacetoxysilane, γ-mercaptopropyltrimethoxysilane, N-β(aminoethyl)-γ-aminopropyltrimethoxysilane, N-β(aminoethyl)-γ-aminopropylmethyldimethoxysilane, γ-ureidopropyltriethoxysilane, bis(β-hydroxyethyl)-γ-aminopropyltriethoxysilane, and γ-aminopropylsilicone, and one or more of these may be used.
[0104] The content of the silane coupling agent is preferably 1 mass% or more based on the total amount of primer layer D, and more preferably 3 mass% or more. If the content of the silane coupling agent is within the above range, it is easier to further improve the adhesion between the primer layer D and the inorganic oxide layer C, and between the primer layer D and the quantum dot-containing layer.
[0105] In addition, in order to suppress crack formation in primer layer D while maintaining good elongation of primer layer D, the content of the silane coupling agent is preferably 30 mass% or less based on the total amount of primer layer D, and more preferably 20 mass% or less.
[0106] Primer layer D may additionally include a filler. The filler serves to improve coating suitability by adjusting the viscosity of the coating solution for forming the primer layer. Examples of fillers may include calcium carbonate, barium sulfate, alumina white, silica, talc, glass frit, resin powder, etc.
[0107] The primer layer may additionally include additives such as stabilizers, crosslinking agents, lubricants, UV absorbers, and others, as needed.
[0108] The total thickness of the inorganic oxide layer A, organic coating layer B, inorganic oxide layer C, and primer layer D is preferably 300 nm or more and 1200 nm or less, more preferably 400 nm or more and 900 nm or less, even more preferably 500 nm or more and 800 nm or less, and even more preferably 550 nm or more and 750 nm or less. By making the total thickness 300 nm or more, it is easier to ensure good barrier properties. In addition, by making the total thickness 1200 nm or less, it is easier to suppress the waveform period of the spectral transmittance becoming excessively short, and to suppress the spectral transmittance of a specific wavelength (e.g., wavelength 450 nm) from changing significantly when the organic coating layer swells and the waveform of the spectral transmittance of the barrier film shifts toward the long wavelength side or the short wavelength side.
[0109] <Physical properties>
[0110] Water vapor permeability
[0111] The barrier film has a water vapor transmittance value of 0.20 g / m² according to JIS K7129-2:2019. 2 It is desirable that it be less than 1 day and 0.15 g / m² 2 · It is more desirable that it be less than day. In addition, the temperature and humidity conditions when measuring water vapor permeability shall be 40℃ and relative humidity 90%. In addition, before measuring water vapor permeability, the sample for measurement shall be exposed to an atmosphere with a temperature of 23℃±5℃ and relative humidity of 40% or more and 65% or less for at least 30 minutes.
[0112] Water vapor permeability can be measured, for example, by a water vapor permeability measuring device manufactured by MOCON (product name: PERMATRAN).
[0113] Oxygen Permeability
[0114] The barrier film has an oxygen permeability value of 0.5 cc / m² according to JIS K7126-2:2006. 2It is preferable that it be less than or equal to day·atm. In addition, the temperature and humidity conditions when measuring oxygen permeability shall be 23℃ and relative humidity 90%. Furthermore, before measuring oxygen permeability, the sample for measurement shall be exposed to an atmosphere with a temperature of 23℃±5℃ and relative humidity of 40% or more and 65% or less for at least 30 minutes.
[0115] Oxygen permeability can be measured, for example, by an oxygen permeability measuring device manufactured by MOCON (product name: OX-TRAN) (Mocon method).
[0116] 《b * value"
[0117] The barrier film is, L * a * b * b of the color system * It is preferable that the value be -1.3 or higher and 1.0 or lower, more preferable that it be -1.5 or higher and 0.8 or lower, and even more preferable that it be -1.0 or higher and 0.5 or lower. In addition, b * The value of transmission b * It is a value. Also, b * When measuring the value, the surface of light incidence is the side opposite to the light-transmitting substrate.
[0118] L * a * b * The color system is L, standardized by the International Commission on Illumination (CIE) in 1976 * a * b * It is based on a color system and is adopted in JIS Z8781-4:2013.
[0119] Total light transmittance
[0120] The barrier film preferably has a total light transmittance of 80% or more according to JIS K7361-1:1997, more preferably 85% or more, and even more preferably 87% or more. In addition, when measuring the total light transmittance, the light incident surface is the side opposite to the light-transmitting substrate.
[0121] Stacked configuration
[0122] As an example of a laminated configuration of the barrier film of the present disclosure, the following (1) can be cited. In the following (1), “ / ” indicates the interface of the layers.
[0123] (1) Light-transmitting substrate / Inorganic oxide layer A / Organic coating layer B / Inorganic oxide layer C / Primer layer D
[0124] To the extent that it does not impede the effects of the present disclosure, the barrier film may have layers other than those described above.
[0125] The barrier film of the present disclosure may also include the laminated configuration of (2) below. However, the laminated configuration of (2) below is disadvantageous in terms of optical properties because it has a larger number of interfaces compared to (1) above, and also the total thickness increases. For this reason, the laminated configuration of (1) above is preferred.
[0126] (2) First light-transmitting substrate / inorganic oxide layer A / organic coating layer B / inorganic oxide layer C / second light-transmitting substrate / primer layer D
[0127] Manufacturing Method
[0128] A barrier film can be manufactured, for example, by forming an inorganic oxide layer A, an organic coating layer B, an inorganic oxide layer C, and a primer layer D in this order on a light-transmitting substrate.
[0129] Inorganic oxide layer A and inorganic oxide layer C can be formed by physical vapor phase growth methods such as vacuum deposition or chemical vapor phase growth methods such as plasma chemical vapor phase growth, as described above.
[0130] The organic coating layer B and the primer layer D can be formed by applying and drying a coating solution in which the composition constituting each layer is dissolved or dispersed, and curing it as needed.
[0131] <Uses>
[0132] The barrier film for a wavelength conversion sheet of the present disclosure can be used, for example, as a barrier film for a wavelength conversion sheet of a surface light source. Examples of surface light sources include a backlight light source of a liquid crystal display device, a backlight light source of an inspection device, etc. That is, the barrier film for a wavelength conversion sheet of the present disclosure can be used as a "barrier film for a wavelength conversion sheet of a backlight light source of a liquid crystal display device," a "barrier film for a wavelength conversion sheet of a backlight light source of an inspection device," etc.
[0133] In addition, the barrier film for wavelength conversion sheets of the present disclosure may also be used as a "barrier film for wavelength conversion sheets in horticulture." Examples of wavelength conversion sheets in horticulture include sheets equipped with a function that converts ultraviolet rays into wavelengths suitable for plant growth. Examples of wavelengths suitable for plant growth include wavelengths suitable for photosynthesis. The wavelength conversion sheets in horticulture may be installed, for example, on the ceilings of horticultural facilities such as vinyl greenhouses and glass rooms.
[0134] [Wavelength Conversion Sheet]
[0135] The wavelength conversion sheet of the present disclosure is a wavelength conversion sheet having a quantum dot containing layer comprising quantum dots and a barrier film laminated on both sides of the quantum dot containing layer, wherein the barrier film is laminated such that the side opposite to the light-transmitting substrate of the barrier film of the present disclosure described above faces toward the quantum dot containing layer.
[0136] FIG. 2 is a cross-sectional view illustrating an embodiment of the wavelength conversion sheet (200) of the present disclosure. The wavelength conversion sheet (200) of FIG. 2 has a quantum dot containing layer (50) containing quantum dots and barrier films (100a, 100b) laminated on both sides of the quantum dot containing layer. Additionally, the wavelength conversion sheet (200) of FIG. 2 is laminated such that the side opposite to the light-transmitting substrate (10) of the barrier films (100a, 100b) faces the quantum dot containing layer (50).
[0137] As shown in FIG. 2, it is preferable for the wavelength conversion sheet to have an upper and lower symmetrical configuration centered on the quantum dot-containing layer. In other words, it is preferable to use a barrier film with the same configuration for the barrier film laminated on both sides of the quantum dot-containing layer. By having the above configuration, deformation is evenly distributed, making it easier to improve the planarity of the wavelength conversion sheet and also making it easier to improve the adhesion of each interface of the wavelength conversion sheet.
[0138] Quantum dot-containing layer
[0139] The quantum dot-containing layer includes quantum dots and binder resin.
[0140] Quantum dots are nanometer-sized semiconductor particles that exhibit unique optical and electrical properties due to the quantum confinement effect (quantum size effect), in which electrons or excitons are trapped within a small, nanometer-sized crystal; they are also referred to as semiconductor nanoparticles or semiconductor nanocrystals.
[0141] Quantum dots are nanometer-sized semiconductor particles, and are not particularly limited as long as they are made of a material that produces a quantum confinement effect (quantum size effect). Examples of quantum dots include semiconductor particles whose emission color is regulated by their particle size, and semiconductor particles having a dopant.
[0142] Quantum dots emit different colors of light depending on their particle size. For example, in the case of a quantum dot composed only of a core made of CdSe, the peak wavelengths of the fluorescence spectrum when the particle size is 2.3 nm, 3.0 nm, 3.8 nm, and 4.6 nm are 528 nm, 570 nm, 592 nm, and 637 nm. That is, the particle size of the quantum dot emitting secondary light with a peak wavelength of 637 nm is 4.6 nm, and the particle size of the quantum dot emitting secondary light with a peak wavelength of 528 nm is 2.3 nm.
[0143] It is preferable that the quantum dot includes one or more types selected from a quantum dot that emits secondary light of a wavelength equivalent to red and a quantum dot that emits secondary light of a wavelength equivalent to green, and it is more preferable that it includes a quantum dot that emits secondary light of a wavelength equivalent to red and a quantum dot that emits secondary light of a wavelength equivalent to green.
[0144] The quantum dot may contain quantum dots other than the quantum dot that emits secondary light of a wavelength equivalent to red and the quantum dot that emits secondary light of a wavelength equivalent to green.
[0145] The content of the quantum dots is appropriately adjusted according to the thickness of the quantum dot-containing layer, the light recycling rate in the backlight, the desired color tone, etc. If the thickness of the quantum dot-containing layer is within the range described below, the content of the quantum dots is approximately 0.01 parts by mass or more and 1.0 parts by mass or less per 100 parts by mass of the binder resin of the quantum dot-containing layer.
[0146] Specifically, as a material serving as the core of a quantum dot, examples may include semiconductor compounds or semiconductor crystals containing semiconductors such as Group II-VI semiconductor compounds like MgS, MgSe, MgTe, CaS, CaSe, CaTe, SrS, SrSe, SrTe, BaS, BaSe, BaTe, ZnS, ZnSe, ZnTe, CdS, CdSe, CdTe, HgS, HgSe, and HgTe; Group III-V semiconductor compounds like AlN, AlP, AlAs, AlSb, GaAs, GaP, GaN, GaSb, InN, InAs, InP, InSb, TiN, TiP, TiAs, and TiSb; and Group IV semiconductors like Si, Ge, and Pb. Additionally, semiconductor crystals containing semiconductor compounds containing three or more elements, such as InGaP, may be used.
[0147] In addition, as a quantum dot composed of semiconductor microparticles having a dopant, Eu in the semiconductor compound 3+, Tb 3+ , Ag + , Cu + Semiconductor crystals formed by doping with cations of rare earth metals or transition metals such as [the above] may also be used.
[0148] As the core material for quantum dots, semiconductor crystals such as CdS, CdSe, CdTe, InP, and InGaP are suitable in terms of ease of fabrication, controllability of particle size for obtaining luminescence in the visible range, and fluorescence quantum yield.
[0149] The quantum dot may be composed of one type of semiconductor compound or two or more types of semiconductor compounds, and may have a core-shell type structure having, for example, a core made of a semiconductor compound and a shell made of a semiconductor compound different from the core.
[0150] When using a core-shell type quantum dot, the luminescence efficiency of the quantum dot can be increased by using a semiconductor material that has a higher bandgap than the semiconductor compound forming the core so that excitons are confined in the core.
[0151] Examples of core-shell structures (core / shell) having such bandgap relationships include CdSe / ZnS, CdSe / ZnSe, CdSe / CdS, CdTe / CdS, InP / ZnS, Gap / ZnS, Si / ZnS, InN / GaN, InP / CdSSe, InP / ZnSeTe, InGaP / ZnSe, InGaP / ZnS, Si / AlP, InP / ZnSTe, InGaP / ZnSTe, InGaP / ZnSSe, etc.
[0152] The size of the quantum dot can be appropriately controlled by the material constituting the quantum dot to obtain light of the desired wavelength. As the particle size of the quantum dot decreases, the energy bandgap increases. In other words, as the crystal size decreases, the emission of the quantum dot shifts toward the blue side, that is, toward the high-energy side. Therefore, by changing the size of the quantum dot, the emission wavelength can be controlled across the entire spectrum of the ultraviolet, visible, and infrared regions.
[0153] In general, the particle size (diameter) of the quantum dot is preferably in the range of 0.5 nm to 20 nm, and particularly preferably in the range of 1 nm to 10 nm. In addition, the narrower the size distribution of the quantum dot, the more vivid the emission color can be obtained.
[0154] The shape of the quantum dot is not particularly limited and may be, for example, spherical, rod-shaped, disc-shaped, or other shapes. If the particle dot is not spherical, the particle diameter of the quantum dot can be the same as that of a true spherical dot having the same volume.
[0155] Quantum dots may be coated with resin.
[0156] Examples of binder resins for the quantum dot-containing layer include thermoplastic resins, cured products of thermosetting resin compositions, and cured products of ionizing radiation-curable resin compositions. Among these, from the perspective of durability, cured products of thermosetting resin compositions and cured products of ionizing radiation-curable resin compositions are preferred, and cured products of ionizing radiation-curable resin compositions are more preferred.
[0157] The thermosetting resin composition is a composition comprising at least a thermosetting resin and is a resin composition that hardens upon heating. In addition to the thermosetting resin, the thermosetting resin composition preferably comprises a thiol compound described below, and more preferably comprises a polyfunctional thiol compound.
[0158] Examples of thermosetting resins include acrylic resin, urethane resin, phenolic resin, urea-melamine resin, epoxy resin, unsaturated polyester resin, silicone resin, etc. In the thermosetting resin composition, a curing agent is added to these curable resins as needed.
[0159] The ionizing radiation curable resin composition is a composition comprising a compound having an ionizing radiation curable functional group (hereinafter also referred to as an "ionizing radiation curable compound"). In addition to the ionizing radiation curable compound, the ionizing radiation curable resin composition preferably comprises a thiol compound described below, and more preferably comprises a polyfunctional thiol compound.
[0160] Examples of ionizing radiation curable functional groups include ethylenically unsaturated bonding groups such as (meth)acryloyl groups, vinyl groups, and allyl groups, as well as epoxy groups and oxetanyl groups, among which ethylenically unsaturated bonding groups are preferred. Furthermore, among ethylenically unsaturated bonding groups, (meth)acrylate groups are preferred. Hereinafter, an ionizing radiation curable compound having (meth)acryloyl groups is referred to as a (meth)acrylate-based compound. That is, it is preferable for the binder resin to include a cured product of a composition containing a (meth)acrylate-based compound.
[0161] In addition, in this specification, “(meth)acrylate” refers to methacrylate and acrylate. In addition, in this specification, “ionizing radiation” means electromagnetic waves or charged particle rays having energy quanta capable of polymerizing or crosslinking molecules, and while ultraviolet rays or electron rays are typically used, other electromagnetic waves such as X-rays and γ-rays, and charged particle rays such as α-rays and ion rays may also be used.
[0162] The ionizing radiation curable compound may be a monofunctional ionizing radiation curable compound having only one of the above-mentioned functional groups, a polyfunctional ionizing radiation curable compound having two or more of the above-mentioned functional groups, or a mixture thereof. Among these, a polyfunctional ionizing radiation curable compound is preferred, and a polyfunctional (meth)acrylate-based compound having two or more (meth)acryloyl groups is more preferred. That is, the binder resin preferably comprises a cured product of a polyfunctional ionizing radiation curable compound, and more preferably comprises a cured product of a polyfunctional (meth)acrylate-based compound. Furthermore, the binder resin preferably comprises a cured product of a composition comprising a polyfunctional ionizing radiation curable compound and a thiol compound, and more preferably comprises a cured product of a composition comprising a polyfunctional (meth)acrylate-based compound and a thiol compound.
[0163] Multifunctional (meth)acrylate compounds may have alkyleneoxy groups.
[0164] As for the alkyleneoxy group, for example, an alkyleneoxy group having 2 or more carbon atoms or less is preferred, an alkyleneoxy group having 2 or 3 carbon atoms is more preferred, and an alkyleneoxy group having 2 carbon atoms is even more preferred.
[0165] A polyfunctional (meth)acrylate compound having an alkyleneoxy group may also be a polyfunctional (meth)acrylate compound having a polyalkyleneoxy group containing a plurality of alkyleneoxy groups.
[0166] When a polyfunctional (meth)acrylate-based compound has alkyleneoxy groups, the number of alkyleneoxy groups in one molecule is preferably 2 or more and 30 or less, more preferably 2 or more and 20 or less, more preferably 3 or more and 10 or less, and even more preferably 3 or more and 5 or less.
[0167] When a polyfunctional (meth)acrylate-based compound has an alkyleneoxy group, it is preferable to have a bisphenol structure. As a result, the heat resistance of the cured product tends to be improved. Examples of bisphenol structures include the bisphenol A structure and the bisphenol F structure, and among these, the bisphenol A structure is preferred.
[0168] Among the polyfunctional (meth)acrylate compounds having an alkyleneoxy group, ethoxylated bisphenol A type di(meth)acrylate, propoxylated bisphenol A type di(meth)acrylate, and propoxylated ethoxylated bisphenol A type di(meth)acrylate are preferred, and ethoxylated bisphenol A type di(meth)acrylate is more preferred.
[0169] In addition, the ionizing radiation curable compound may be a monomer, an oligomer, a low molecular weight polymer, or a mixture thereof.
[0170] As described above, the thermosetting resin composition and the ionizing radiation curable resin composition preferably include a thiol compound.
[0171] A thiol compound is a compound having one or more units represented by R-SH (where R is an organic group). In this specification, a compound having one unit represented by R-SH is referred to as a monofunctional thiol compound, and a compound having two or more units represented by R-SH is referred to as a polyfunctional thiol compound.
[0172] The thiol compound may be a monofunctional thiol compound, but a polyfunctional thiol compound is preferred from the perspective of improving the strength of the quantum dot-containing layer. Furthermore, among polyfunctional thiol compounds, a trifunctional thiol compound or a tetrafunctional thiol compound is more preferred.
[0173] A thiol compound undergoes a thiol-ene reaction with a compound having a radical polymerizable functional group in the presence of a radical polymerization initiator according to the following formula. Since the thiol-ene reaction can suppress polymerization shrinkage, it is desirable in that it relieves stress generated during the curing of the quantum dot-containing layer, and as a result, it is easier to further improve the interlayer adhesion of the wavelength conversion sheet. In addition, the cured product obtained by the thiol-ene reaction is desirable in that it is easy to achieve good heat resistance. Furthermore, since the refractive index of the thiol compound (about 1.53) is higher than that of the polyfunctional (meth)acrylate-based compound (about 1.45), the degree of freedom in adjusting the refractive index of the quantum dot-containing layer can be increased.
[0174] In addition, the following reaction is an example of a reaction between a monofunctional thiol compound and a compound having one radical polymerizable functional group. It is thought that the reaction product of a polyfunctional thiol compound and a compound having two or more radical polymerizable functional groups is likely to form a dendrimer structure. Furthermore, it is thought that when a dendrimer structure is formed, the flexibility of the quantum dot-containing layer increases, and the quantum dot-containing layer itself becomes more likely to exhibit excellent stress relaxation properties. Examples of radical polymerizable functional groups include ethylenically unsaturated bond-containing groups such as (meth)acryloyl groups, vinyl groups, and allyl groups.
[0175]
[0176] [In the middle of the meal, R 1 and R 2 is an organic device.]
[0177] Specific examples of monofunctional thiol compounds include hexanethiol, 1-heptanethiol, 1-octanthiol, 1-nonanthiol, 1-decanethiol, 3-mercaptopropionic acid, methyl mercaptopropionic acid, methoxybutyl mercaptopropionic acid, octyl mercaptopropionic acid, tridecyl mercaptopropionic acid, 2-ethylhexyl-3-mercaptopropionate, n-octyl-3-mercaptopropionate, etc.
[0178] Specific examples of polyfunctional thiol compounds include ethylene glycol bis(3-mercaptopropionate), diethylene glycol bis(3-mercaptopropionate), tetraethylene glycol bis(3-mercaptopropionate), 1,2-propylene glycol bis(3-mercaptopropionate), diethylene glycol bis(3-mercaptobutyrate), 1,4-butanediol bis(3-mercaptopropionate), 1,4-butanediol bis(3-mercaptobutyrate), 1,8-octanediol bis(3-mercaptopropionate), 1,8-octanediol bis(3-mercaptobutyrate), hexanediol bisthioglylate, trimethylolpropane tris(3-mercaptopropionate), trimethylolpropane tris(3-mercaptobutyrate), and trimethylolpropane tris(3-mercaptoisobutyrate). Trimethylolpropane tris(2-mercaptoisobutyrate), trimethylolpropane trithioglycolate, tris[(3-mercaptopropionyloxy)-ethyl]-isocyanurate, trimethylolethanetris(3-mercaptobutyrate), pentaerythritol tetrakis(3-mercaptopropionate), pentaerythritol tetrakis(3-mercaptobutyrate), pentaerythritol tetrakis(3-mercaptoisobutyrate), pentaerythritol tetrakis(2-mercaptoisobutyrate), dipentaerythritol hexakis(3-mercaptopropionate), dipentaerythritol hexakis(2-mercaptopropionate), dipentaerythritol hexakis(3-mercaptobutyrate), dipentaerythritol hexakis(3-mercaptoisobutyrate), Examples include dipentaerythritol hexakis(2-mercaptoisobutyrate), pentaerythritol tetrakisthioglycolate, dipentaerythritol hexakisthioglycolate, etc.
[0179] In an ionizing radiation-curable resin composition (or thermosetting resin composition), the mass ratio of the ionizing radiation-curable compound (or thermosetting resin) to the thiol compound is preferably 80:20 to 35:65, and more preferably 70:30 to 40:60.
[0180] When the ionizing radiation curable compound is a UV-curable compound, it is preferable that the ionizing radiation curable composition include additives such as photopolymerization initiators or photopolymerization promoters.
[0181] The quantum dot-containing layer may contain internally diffused particles.
[0182] Internal diffusion particles can be either organic or inorganic particles. Examples of organic particles include particles composed of polymethyl methacrylate, acrylic-styrene copolymer, melamine resin, polycarbonate, polystyrene, polyvinyl chloride, benzoguanamine-melamine-formaldehyde condensate, silicone resin, fluorinated resin, and polyester. Examples of inorganic fine particles include fine particles composed of silica, alumina, zirconia, and titania.
[0183] Examples of internal diffusion particles include spherical, disc-shaped, rugby ball-shaped, and irregular shapes. Additionally, the internal diffusion particles may be any of hollow particles, porous particles, or solid particles.
[0184] The content of internal diffusion particles is preferably 1 part by mass or more and 40 parts by mass or less per 100 parts by mass of binder resin, and more preferably 3 parts by mass or more and 30 parts by mass or less.
[0185] The average particle size of the internal diffusion particles is preferably 1 μm or more and 7 μm or less, and more preferably 1 μm or more and 3 μm or less.
[0186] The thickness of the quantum dot-containing layer is preferably 10 μm or more and 200 μm or less, more preferably 20 μm or more and 150 μm or less, and even more preferably 30 μm or more and 130 μm or less.
[0187] Refractive index n of the quantum dot-containing layer ZIt is preferable that it be 1.40 or more and 1.55 or less, more preferable that it be 1.43 or more and 1.52 or less, and even more preferable that it be 1.46 or more and 1.50 or less.
[0188] Refractive index n of the quantum dot-containing layer Z This is roughly governed by the refractive index of the binder resin. This is because the quantum dot-containing layer has a low quantum dot content, and even if an internal diffusion agent is included, the particle size of the internal diffusion agent is larger than the wavelength of light and does not affect the refractive index of the layer.
[0189] [Backlight]
[0190] The backlight of the present disclosure comprises at least one light source emitting primary light, an optical plate disposed adjacent to the light source for guiding or diffusing light, and a wavelength conversion sheet disposed on the light-emitting side of the optical plate, wherein the wavelength conversion sheet is the wavelength conversion sheet of the present disclosure described above.
[0191] As for the backlight (300) of the present disclosure, an edge light type backlight (301) as shown in FIG. 3 or a direct light type backlight (302) as shown in FIG. 4 may be cited as examples.
[0192] The optical plate (220) used in the edge-light type backlight (301) of FIG. 3 is an optical member for guiding primary light emitted from a light source (210), and is a so-called light guide plate (221). The light guide plate (221) is formed in a roughly flat shape, for example, such that at least one surface is formed as a light incident surface and one surface approximately orthogonal to it is formed as a light exit surface.
[0193] The light guide plate is composed of a matrix resin selected primarily from highly transparent resins such as polymethyl methacrylate. If necessary, resin particles with a different refractive index from the matrix resin may be added to the light guide plate. Each surface of the light guide plate may not be a uniform flat surface but may have a complex surface shape, or may have dot patterns formed thereon.
[0194] The optical plate (220) used in the direct-type backlight (302) of FIG. 4 is an optical member (light-diffusing plate (222)) having light-diffusing properties to make it difficult to see the pattern of the light source (210). As for the light-diffusing plate (222), for example, a milky white resin plate with a thickness of about 1 mm or more and 3 mm or less can be used.
[0195] In addition to the light source, optical plate, and barrier film described above, edge-light type and direct-light type backlights may also be equipped with one or more components selected from a reflector, a light-diffusing film, a prism sheet, a brightness-increasing film (BEF), and a reflective polarizing film (DBEF), depending on the purpose.
[0196] A reflector is positioned on the side opposite to the light-emitting surface of the optical plate. A light-diffusing film, a prism sheet, a brightness-increasing film, and a reflective polarizing film are positioned on the light-emitting surface of the optical plate. By configuring the backlight to include one or more components selected from a reflector, a light-diffusing film, a prism sheet, a brightness-increasing film, and a reflective polarizing film, it is possible to produce a backlight with excellent balance of front brightness, viewing angle, etc.
[0197] In edge-light type and direct-type backlights, the light source (210) is a light-emitting body that emits primary light, and it is preferable to use a light-emitting body that emits primary light of a wavelength equivalent to blue. The primary light of a wavelength equivalent to blue preferably has a peak wavelength in the range of 380 nm or more and 480 nm or less. It is more preferable that the peak wavelength be 450 nm ± 7 nm, more preferable that it be 450 nm ± 5 nm, more preferable that it be 450 nm ± 3 nm, and more preferable that it be 450 nm ± 1 nm.
[0198] As for the light source (210), it is preferable that it be an LED light source in the view that the device for installing the backlight can be simplified and miniaturized, and it is more preferable that it be a blue single-color LED light source. The light source (210) is at least one, and it is preferable that there be multiple sources in the view that it emits sufficient primary light.
[0199] A backlight including a wavelength conversion sheet preferably has a difference in x value (Δx) and a difference in y value (Δy) before and after the following high temperature and high humidity test with respect to the Yxy color system of the International Commission on Illumination (CIE), which is 0.015 or less, and more preferably 0.010 or less. By making Δx and Δy 0.020 or less, changes in color tone can be suppressed.
[0200] High Temperature and High Humidity Test: Test of exposure to an atmosphere of 60°C and 90% relative humidity for 1,000 hours
[0201] In addition, the x and y values after the high temperature and high humidity test are to be measured quickly in an atmosphere with a temperature of 23℃±5℃ and a relative humidity of 40% or more and 65% or less after removing the sample for measurement from the high temperature and high humidity test environment.
[0202] [Liquid Crystal Display]
[0203] The liquid crystal display device of the present disclosure is a liquid crystal display device comprising a backlight and a liquid crystal panel, wherein the backlight is the backlight of the present disclosure described above.
[0204] The liquid crystal panel is not particularly limited, and a general-purpose liquid crystal panel can be used as the liquid crystal panel of the liquid crystal display device. For example, a liquid crystal panel having a general structure in which glass plates are sandwiched between the upper and lower liquid crystal layers, specifically a display method such as TN, STN, VA, IPS, and OCB, can be used.
[0205] The liquid crystal display device also includes a polarizing plate and a color filter, etc. General-purpose polarizing plates and color filters may be used.
[0206] The image displayed in a liquid crystal display is displayed in color as white light irradiated from a backlight passes through a color filter. By utilizing a color filter suitable for the spectrum of the backlight generated by quantum dots, the liquid crystal display can realize a display that produces very vivid colors with excellent brightness and efficiency.
[0207] Examples
[0208] Next, the present disclosure will be explained in more detail by way of examples, but the present disclosure is not limited in any way by these examples. Here, “parts” and “%” are based on mass unless specifically asked for permission.
[0209] 1. Measurement and Evaluation
[0210] The following measurements and evaluations were performed on the barrier films or wavelength conversion sheets of the examples and comparative examples. The results are shown in Table 1 or Table 2.
[0211] 1-1. Water Vapor Permeability
[0212] Water vapor permeability values were measured for the barrier films of the Examples and Comparative Examples according to JIS K7129-2:2019. The measuring device used was the "PERMATRAN" manufactured by MOCON. The temperature and humidity conditions for measuring water vapor permeability were set to 40°C and 90% relative humidity. In addition, prior to measuring water vapor permeability, the sample for measurement was exposed to an atmosphere with a temperature of 23°C ± 5°C and a relative humidity of 40% to 65% for at least 30 minutes. The water vapor permeability measured in this manner represents the water vapor permeability at the initial stage. The water vapor permeability was 0.20 g / m². 2 ·day or less is the passing level.
[0213] 1-2. Total Light Transmittance
[0214] The total light transmittance was measured for the barrier films of the examples and comparative examples. The light incident surface was the side opposite to the light-transmitting substrate. A haze meter (HM-150, manufactured by Murakami Shikisaigi Jutsu Genkyusho) was used as the measuring device. A total light transmittance of 85% or higher is the acceptable level.
[0215] In addition, total light transmittance was measured in an atmosphere with a temperature of 23℃±5℃ and a relative humidity of 40% or higher and 65% or lower. Furthermore, the sample was exposed to the above atmosphere for at least 30 minutes prior to measurement. The total light transmittance measured in this manner represents the total light transmittance at the initial stage.
[0216] 1-3. b * value
[0217] Regarding the barrier films of the examples and comparative examples, L * a * b * b of the color system * Value (transmission b) * The value) was measured. The light incident surface was set to the side opposite to the light-transmitting substrate. A spectrophotometer manufactured by Nippon Bunko Co., Ltd. (Product name: V670) was used as the measuring device. b * A value of -1.3 or higher and 1.0 or lower is the passing level.
[0218] Also, b * The values were measured in an atmosphere with a temperature of 23℃±5℃ and a relative humidity of 40% to 65%. In addition, the sample was exposed to the said atmosphere for at least 30 minutes prior to measurement. The b measured in this manner * The value is b in the initial stage. * It means value.
[0219] 1-4. Δx, Δy
[0220] <Preparation of Direct-type Backlight for Measurement>
[0221] A commercially available liquid crystal television (manufactured by VIZIO, PQ65-F1) equipped with a direct-type backlight was disassembled and the direct-type backlight was removed. The direct-type backlight is equipped with a direct-type blue LED as a light source, having a center wavelength of 450 nm and a full width at half maximum of 20 nm. Additionally, on the light emission side of the light source, a light diffusion plate, a wavelength conversion sheet including a quantum dot-containing layer, a prism sheet, and a reflective polarizer (brightness enhancement film, manufactured by 3M, DBEF (registered trademark)) are arranged in this order. Furthermore, a reflective sheet is provided on the side opposite to the light emission side of the light source.
[0222] The wavelength conversion sheet inside the above direct-type backlight was changed to the wavelength conversion sheet of the example and comparative example to obtain a "direct-type backlight for measuring x and y values in the initial stage." In addition, the wavelength conversion sheet of the example and comparative example was exposed to an atmosphere with a temperature of 23℃±5℃ and a relative humidity of 40% or more and 65% or less for at least 30 minutes before being inserted into the direct-type backlight.
[0223] In addition, the wavelength conversion sheet inside the above direct-type backlight was changed to the wavelength conversion sheet of the example and comparative example that underwent a high temperature and high humidity test (a test of exposure to an atmosphere of 60°C and 90% relative humidity for 1000 hours) to obtain a "direct-type backlight for measuring x and y values after a high temperature and high humidity test." The process of inserting the wavelength conversion sheet of the example and comparative example that underwent the high temperature and high humidity test into the direct-type backlight was carried out quickly in an atmosphere with a temperature of 23°C ± 5°C and a relative humidity of 40% or more and 65% or less.
[0224] In addition, regarding the aforementioned direct-type backlight for measurement, measurements were performed under the following measurement environment.
[0225] <Initial stage x and y values>
[0226] A direct-type backlight for measuring x and y values in the initial stage was turned on, and the x and y values of the International Commission on Illumination (CIE) Yxy color system were measured from a frontal direction 500 mm away in a dark room environment. The measurement atmosphere was set to a temperature of 23℃±5℃ and a relative humidity of 40% or more and 65% or less. In addition, the sample was exposed to the above atmosphere for at least 30 minutes prior to measurement. The measurement device used was a spectroradiometer (product name: SR-3AR) manufactured by Topcon Technohouse.
[0227] <x and y values after high temperature and high humidity test>
[0228] After the high temperature and high humidity test, a direct-type backlight was turned on to measure the x and y values, and under a dark room environment, the x and y values of the International Commission on Illumination (CIE) Yxy color system were measured from a frontal direction 500 mm away. The measurement atmosphere was set to a temperature of 23℃±5℃ and a relative humidity of 40% or higher and 65% or lower. The measurement device used was a spectroradiometer (product name: SR-3AR) manufactured by Topcon Technohouse.
[0229] <Δx, Δy>
[0230] The difference between the x value at the initial stage and the x value after the high temperature and high humidity test (Δx) and the difference between the y value at the initial stage and the y value after the high temperature and high humidity test (Δy) were calculated. A passing level is when both Δx and Δy are 0.015 or less.
[0231] 2. Preparation of Quantum Dot Dispersion
[0232] In a glove box purged with nitrogen to reduce the oxygen concentration to 300 ppm or less, quantum dots and amino-modified silicon were mixed in the compositional ratios shown below, and stirred with a magnetic stirrer for 4 hours while heating in a water bath at 90°C. Afterward, the mixture was filtered through a polypropylene filter with a pore diameter of 0.2 μm to obtain a CdSe / ZnS core-shell type quantum dot dispersion.
[0233] · Quantum dot 0.9 mass part
[0234] (Emission peak: 540 nm, Manufacturing number: 748056, Manufactured by Sigma-Aldrich)
[0235] · Quantum dot 0.9 mass part
[0236] (Emission peak: 630 nm, Manufacturing number: 790206, Manufactured by Sigma-Aldrich)
[0237] · Amino-modified silicon 99 parts by mass
[0238] (Manufactured by Genesee, Part No.: GP-344, Viscosity: 670 mPa·s)
[0239] 3. Fabrication of barrier films and wavelength conversion sheets
[0240] [Example 1]
[0241] Aluminum oxide is deposited by vacuum deposition on one side of a biaxially stretched PET film (refractive index n0: 1.636, thickness t0: 12 μm) to form an inorganic oxide layer A (refractive index n A : 1.77, thickness t A : 8 nm) formed.
[0242] Next, a coating solution for forming the following organic coating layer is applied onto the inorganic oxide layer A by gravure printing, and heat-treated at 180°C for 60 seconds to form the organic coating layer B (refractive index n B : 1.55, thickness t B : formed 219 nm).
[0243] Subsequently, aluminum oxide is deposited on the organic coating layer B by vacuum deposition to form an inorganic oxide layer C (refractive index n C : 1.77, thickness t C : 8 nm) formed.
[0244] Next, the following coating solution 1 for forming a primer layer is applied onto the inorganic oxide layer C by gravure printing, heat-treated at 80°C for 60 seconds, and primer layer D (refractive index n D : 1.575, thickness t E A barrier film of Example 1 was obtained by forming a (270 nm) layer. In addition, two barrier films of the same composition were prepared.
[0245] <Preparation of Coating Solution for Forming Organic Coating Layers>
[0246] Solution A was prepared by mixing tetraethoxysilane with a solution (pH 2.2) of water, isopropyl alcohol, and 0.5N hydrochloric acid while cooling to 10°C. Separately, Solution B was prepared by mixing polyvinyl alcohol with a saponification of 99% or more and isopropyl alcohol. Solution A and Solution B were mixed to prepare a coating solution for forming an organic coating layer (solid content: 5 mass%). In the coating solution for forming an organic coating layer, the mass ratio of tetraethoxysilane to polyvinyl alcohol is 29:4.
[0247] <Coating Solution for Forming Primer Layer 1>
[0248] · 50 parts by mass of polyester polyurethane polyol
[0249] (Hydroxyl value: 62 mgKOH / g, Solids content 20 mass%)
[0250] · 1 part by mass of silane coupling agent
[0251] (3-Glycidoxypropylmethyldimethoxysilane)
[0252] · Silica filler 1 part by mass
[0253] (Average particle size 5 µm)
[0254] · 1 part by mass of hardener
[0255] (1,6-hexamethylene diisocyanate, solids 35%)
[0256] · 50 parts by mass of solvent
[0257] (methyl ethyl ketone)
[0258] A laminate A was obtained by applying a quantum dot-containing layer coating solution of the following formulation to the primer layer side of one of the two barrier films produced above, drying it, and forming a quantum dot-containing layer of ionizing radiation-free irradiation.
[0259] Next, the laminate A was laminated such that the side of the quantum dot-containing layer that is not irradiated with ionizing radiation and the side of the primer layer of the other barrier film faced each other, and then ultraviolet light was irradiated and the curing of the ionizing radiation-curable resin composition of the quantum dot-containing layer was carried out to obtain the wavelength conversion sheet of Example 1. The thickness of the quantum dot-containing layer is 100 μm, and the refractive index is 1.48.
[0260] Quantum Dot-Containing Layer Coating Solution
[0261] · Polyfunctional acrylate compound 58.11 parts by mass
[0262] (Ethoxylated bisphenol A diacrylate; Shinnakamura Kagaku Kogyo Co., Ltd. product name "ABE-300")
[0263] · Multifunctional thiol compound 38.74 parts by mass
[0264] (Pentaerythritol tetrakis(3-mercaptopropionate); SC Yukikagaku Co., Ltd. trade name "PEMP")
[0265] · 0.5 parts by mass of photopolymerization initiator
[0266] (Product name of IGM Resins BV: "Omnirad TPO H")
[0267] · 1.61 parts by mass of the quantum dot dispersion prepared in "2" above
[0268] · 0.79 parts by mass of acetic acid
[0269] · 0.25 parts by mass of titanium oxide
[0270] (Chemours trade name "TyPure R-706"; particle size 0.36 µm)
[0271] [Examples 2–14]
[0272] Barrier films and wavelength conversion sheets of Examples 2 to 14 were obtained by following the same procedure as in Example 1, except that the thicknesses of the organic coating layer B and the primer layer D were changed to the values in Table 1.
[0273] However, the primer layers of Examples 9 to 14 were formed using the following coating solution 2 for forming a primer layer. In addition, the refractive index n of the primer layers of Examples 9 to 14 D It was 1.58.
[0274] <Coating Solution for Primer Layer Formation 2>
[0275] · 50 parts by mass of polyester polyurethane polyol
[0276] (Hydroxyl value: 52 mgKOH / g, Solids content 20 mass%)
[0277] · 1 part by mass of silane coupling agent
[0278] (3-Glycidoxypropylmethyldimethoxysilane)
[0279] · Silica filler 1 part by mass
[0280] (Average particle size 5 µm)
[0281] · 1 part by mass of hardener
[0282] (1,3-Xylene diisocyanate, solids 35%)
[0283] · 50 parts by mass of solvent
[0284] (methyl ethyl ketone)
[0285] [Examples 15–16]
[0286] Barrier films and wavelength conversion sheets of Examples 15 and 16 were obtained in the same manner as in Example 1, except that inorganic oxide layer A and inorganic oxide layer C were changed to silicon oxide deposition films (refractive index: 1.457) and the thicknesses of inorganic oxide layer A, organic coating layer B, inorganic oxide layer C, and primer layer D were changed to the values in Table 1.
[0287] [Comparative Example 1]
[0288] A barrier film and wavelength conversion sheet of Comparative Example 1 were obtained by forming a primer layer D on an organic coating layer B and not forming an inorganic oxide layer C, in the same manner as in Example 1.
[0289] [Comparative Examples 2–15]
[0290] Barrier films and wavelength conversion sheets of Comparative Examples 2 to 15 were obtained by following the same procedure as in Example 1, except that the thicknesses of the organic coating layer B and the primer layer D were changed to the values in Table 2.
[0291] However, the primer layers of Comparative Examples 12 to 15 were formed using the above-described coating solution 2 for forming a primer layer. In addition, the refractive index n of the primer layers of Comparative Examples 12 to 15 D It was 1.58.
[0292]
[0293]
[0294] As is evident from the results of Tables 1 and 2, it can be confirmed that the barrier film of the example can suppress changes in color when applied to a wavelength conversion sheet.
[0295] On the other hand, it can be confirmed that the barrier film of the comparative example cannot suppress changes in color when applied to a wavelength conversion sheet. The barrier film of Comparative Example 1, t Bis 150 nm or more and 500 nm or less, and also t D / t B Although the value is between 0.55 and 1.65, because it does not have an inorganic oxide layer C, the barrier performance is inferior, and it was not possible to suppress changes in color. The barrier films of Comparative Examples 2 to 15, t B and t D / t B Because at least one of them was outside the specified range, it was impossible to suppress the change in color. Explanation of the symbols
[0296] 10: Light-transmitting substrate, 21: Inorganic oxide layer A, 22: Inorganic oxide layer C, 30: Organic coating layer B, 40: Primer layer D, 50: Quantum dot containing layer, 100: Barrier film, 100a: Barrier film, 100b: Barrier film, 200: Wavelength conversion sheet, 210: Light source, 220: Optical plate, 221: Light guide plate, 222: Diffusion plate, 230: Reflector, 240: Prism sheet, 300: Backlight, 301: Edge-light type backlight, 302: Direct-type backlight.
Claims
Claim 1 On a light-transmitting substrate, an inorganic oxide layer A, an organic coating layer B, an inorganic oxide layer C, and a primer layer D are arranged in this order, and the thicknesses of the light-transmitting substrate, the inorganic oxide layer A, the organic coating layer B, the inorganic oxide layer C, and the primer layer D are respectively t0 and t A , t B , t C and t D When defined as, t B α is 150 nm or more and 450 nm or less, and also, t D / t B A barrier film for wavelength conversion sheets having a value of 0.55 or higher and 1.65 or lower. Claim 2 A barrier film according to claim 1, wherein the inorganic oxide layer A and the inorganic oxide layer C comprise aluminum oxide or silicon oxide. Claim 3 A barrier film according to claim 1 or 2, wherein the organic coating layer B comprises polyvinyl alcohol. Claim 4 A wavelength conversion sheet having a quantum dot containing layer including quantum dots and a barrier film laminated on both sides of the quantum dot containing layer, wherein the barrier film is laminated such that the side opposite to the light-transmitting substrate of the barrier film described in claim 1 or 2 faces the quantum dot containing layer. Claim 5 A backlight comprising at least one light source emitting primary light, an optical plate disposed adjacent to the light source for guiding or diffusing light, and a wavelength conversion sheet disposed on the light-emitting side of the optical plate, wherein the wavelength conversion sheet is the wavelength conversion sheet described in claim 4. Claim 6 A liquid crystal display device having a backlight and a liquid crystal panel, wherein the backlight is the backlight described in claim 5.
Citation Information
Patent Citations
Composition for primer layer formation, barrier film, wavelength conversion sheet, and method for producing wavelength conversion sheet
JP2019044136A
Light-emitting body protection film and method for manufacturing same, wavelength conversion sheet, and light emission unit
WO2017126609A1
Barrier film, wavelength conversion sheet using the same, and display
JP2017100350A
Gas barrier film and wavelength conversion film
JP2017159576A